Overexpression of lncRNA H19 changes basic characteristics and affects immune response of bovine mammary epithelial cells - Li, Xuezhong; Wang, Hao; Zhang, Yanfen; Zhang, Jinjing; Qi, Shaopei; Zhang, Yong; Gao, Ming-Qing (PeerJ, 2019)
The function of long non-coding RNA H19 (H19) on cell proliferation has been observed in various cell types, and the increased expression of H19 was also found in the lipopolysaccharide (LPS)-induced inflammatory bovine mammary epithelial cells (MAC-T). However, the roles of H19 in the inflammatory response and physiological functions of bovine mammary epithelial cell are not clear. In the present study, we found that overexpression of H19 in MAC-T cells significantly promoted cell proliferation, increased the protein and mRNA level of β-casein, and enhanced the expression of tight junction (TJ)-related proteins while inhibited staphylococcus aureus adhesion to cells. In addition, results demonstrated that overexpression of H19 affected the LPS-induced immune response of MAC-T cells by promoting expressions of inflammatory factors, including TNF-α, IL-6, CXCL2 and CCL5, and activating the NF-κB signal pathway. Our findings indicate that H19 is likely to play an important role in maintaining normal functions and regulating immune response of bovine mammary epithelial cells.
Keywords: Bovine mastitis; Epithelial cells; Long non-coding RNA H19; Lipopolysaccharide; Immnue response